Commercial Code, he should be or not to be? Part 1 - Юлдашев, Сергей Алексеевич (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The problems associated with the adoption and operation of the Commercial Code of Ukraine, the dualism in the legal regulation of property relations. The history of the emergence of the economic rights, one of the possible methodological approaches to improving the legal regulation of economic activity, solving the problem of inconsistency of the Commercial Code, the Civil and the direction of the first decision on the main actual problems of the economy. The main issue, considered in the article, is the answer to the question about expediency of keeping (or abolition) of the Commercial Code (CC) of Ukraine. There are a lot of articles devoted to the issue «Should the Commercial Code exist or not». The purpose of this article is to form some guidelines for improving the CC and to define rules for the use of its provisions. Modern scientists, who supported the adoption of the Commercial Code, were assuring the government and society that the adoption of the Commercial Code, which was supposed to form the basis for the beginning of economic and legal regulation, would be able to eliminate the gaps in the economic law and supply that which was lacking in it’s consistency and fragmented approach. The main motivations for the revival of demand for Commercial Code regulation became the following reasons: revitalization of private property and private entrepreneurship, raising of freedom of agreement (instead of directive planning) to the rank of concepts of economical (entrepreneur) activity and the need of it’s legalisation, introduction of variety of types of ownership and various organisational and legal forms of entrepreneurial activities etc. It has taken about ten years to prepare the CC, which has been processed in conjunction with the Project of the Civil Code. The preparation of the mentioned documents was conducted autonomously and in local mode, without any kind of coordination, and moreover in conditions of some kind of competition and mutual dislike. The legal community of the country knows very well the confrontation between «businessmen» and «civilians», which took place in those years. However, country’s interests and economic development required the systemic coordination and unification of efforts towards the Commercial Code and Civil code development. It was necessary to coordinate this work at all stages – starting with the development of conceptual provisions and ending with the coordinated processing of one-dimensional sections and regulations. After the adoption of the CC in 2003 (at the same time with the Civil Code), the issue of it’s abolition has repeatedly raised in the country. Considering the case of should the Commercial Code exist or not, already in 2008 it was suggested that a certain New Business Code ( The symbiosis of Commercial and Civil ones) should be made. Most of experts agreed that the abolition of the CC may end up in a vacuum in some legal regulations. It was suggested that despite of all weaknesses of the CC, it’s abolition may become a big mistake. Main argument is that the existing CC allowed the development of the clear «rules of the game» for entrepreneurs and established a common legal practice. Therefore, the improvement of the norms to the existing Code might become a solution to remedy this situation.